2022
DOI: 10.7759/cureus.21186
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation Versus Closed Reduction and Maxillomandibular Fixation of Condylar Fractures of the Mandible: A Prospective Study

Abstract: BackgroundThe choice of surgical versus nonsurgical treatment for fractures of the condylar process has its own limitations and remains a controversial issue. Improved knowledge of anatomy, technique, and technology combined with adequate experience with careful planning of surgical technique can avoid all the possible complications. AimTo compare open reduction and internal fixation with closed reduction and maxillomandibular fixation in the management of condylar fractures. Materials and methodA prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Our clinical findings show significant improvements in TMJ function and pain between T1 and T2, with no severe TMJ disorders or medium-term complications at T2. Despite the anesthesiologic risk, additional expenses, and necessary surgeon training, our study findings support the open treatment of CHF and the findings of previous studies with low resorption and good clinical patient outcomes [ 14 , 16 , 19 , 20 , 29 ]. Therefore, we strongly recommend the open treatment for displaced condylar head fractures, as it is still not widely performed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our clinical findings show significant improvements in TMJ function and pain between T1 and T2, with no severe TMJ disorders or medium-term complications at T2. Despite the anesthesiologic risk, additional expenses, and necessary surgeon training, our study findings support the open treatment of CHF and the findings of previous studies with low resorption and good clinical patient outcomes [ 14 , 16 , 19 , 20 , 29 ]. Therefore, we strongly recommend the open treatment for displaced condylar head fractures, as it is still not widely performed.…”
Section: Discussionsupporting
confidence: 89%
“…A latest clinical trial showed that open treatment seems to be clearly superior to conservative treatment in terms of clinical function [ 29 ]. The information on clinical function and outcome in our study is limited due to its medium-term follow-up of 15 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P value is < 0.001 which indicated highly significant difference between both the groups. In open reduction group Similar results were achieved by Prakash R Sr et al 24 over 6 months after the surgery (37.36mm). Thus, major concern after conservative treatment is restricted mouth opening.…”
Section: Stability Of Fractured Fragment and Osteosynthesis Devicesupporting
confidence: 83%
“…In general, ORIF is suggested to lead to better occlusal results, anatomic restoration and faster recovery rates than non‐surgical techniques 1 . Other studies suggest that open surgical treatment should be indicated in cases of displaced and dislocated condylar fractures 5 . Nevertheless, potential surgical complications such as facial nerve palsy, salivary fistula and deranged occlusion cannot be denied 5,6 .…”
Section: Introductionmentioning
confidence: 99%